Mechanistic insights curcumin’s anti-inflammatory in pancreatic cancer: experimental and computational evidence implicating IL1B interference via IL10RA upregulation and NLRP3/TLR3 downregulation - Cao, Jun-Feng; Hang, Kuan; Zhang, Hao; Xia, Qingjie; Zhang, Xiao; Men, Jie; Tian, Jin; Xia, Zengliang; Liao, Dunshui; Li, Kezhou (Frontiers in Cell and Developmental Biology, 2025)
PurposePancreatic cancer is a highly aggressive malignancy characterised by a complex tumour microenvironment and chronic inflammation. Studies found curcumin inhibited with inflammatory responses and tumour proliferation by interfering with production and activation of pro-inflammatory factors. This study investigated curcumin treated pancreatic cancer by modulating key targets in the inflammatory response and their signalling pathways.MethodsThe human pancreatic cancer PL45 cells and SUIT-2 cells were utilized to establish cellular experiments, and the effects of curcumin on proliferation, apoptosis and cell migration of PL45 cells and SUIT-2 cells were detected by CCK-8, Annexin V-FITC/PI and cell scratching experiment. PL45 cells RNA from experimental and control groups was also analyzed by transcriptome sequencing. Bioinformatics screening of differential gene targets in transcriptome sequencing was performed. Gene Ontology, KEGG and Protein-protein interaction were used to analyze the differentially expressed targets at the gene level and protein level, respectively. We validated the differential gene targets by machine learning analysis of GSE28735 data, and performed survival analysis, pan-tumor analysis, immune infiltration analysis and single-cell transcriptional analysis on the differentially expressed targets. Computer simulations were utilized to verify the stability of curcumin binding to key proteins.ResultsResults of cellular experiments suggested 30 μg/mL curcumin and 50 μg/mL curcumin significantly inhibited the proliferation and growth of PL45 and SUIT-2, respectively. The transcriptome results indicated that 2,676 genes showed differential expression in curcumin-treated group compared to control group. Bioinformatics and machine learning analyses screened 14 key targets that are closely related to the inflammatory response in pancreatic cancer. Molecular dynamics showed binding free energies for IL1B/Curcumin, IL10RA/Curcumin, NLRP3/Curcumin and TLR3/Curcumin were −12.76 ± 1.41 kcal/mol, −11.42 ± 2.57 kcal/mol, −28.16 ± 3.11 kcal/mol and −12.54 ± 4.80 kcal/mol, respectively.ConclusionThis research findings indicated that curcumin not only directly interfered with the activation of IL1B through blocking activation of NLRP3 by TLR3, but also upregulated expression of IL10RA to activate IL-10, thereby interfering with IL1B and its downstream signalling pathway.